The Global Prevalence of and Factors Associated with Parasitic Coinfection in People Living with Viruses: A Systematic Review and Meta-Analysis - Yan Ge; Huaman Liu; Ningjun Ren; Abdul Qadeer; Ian Kim B. Tabios; Ian Kendrich C. Fontanilla; Lydia R. Leonardo; Banchob Sripa; Guofeng Cheng (Pathogens)
Coinfection with parasites and viruses can exacerbate disease transmission, outcomes and therapy. This study searched the Web of Science, PubMed, Scopus and JSTOR databases for publications on the prevalence of parasitic coinfection in people living with viruses from 1 January 2005 to 30 April 2022, and 356 studies were included and systematically reviewed. A meta-analysis was performed to assess the global prevalence of and factors potentially associated with parasitic infection (helminths and protozoa) in virus-infected people, and the infection burden was estimated. A variety of parasites (29 families, 39 genera, and 63 species) and viruses (8 kinds) were identified. The prevalence of parasitic coinfection in (all) virus-infected people was estimated to be 21.34% (95% CI 17.58–25.10, 5593 of 29,190 participants) and 34.13% (95% CI 31.32–36.94, 21,243/76,072 participants) for helminths and protozoa, respectively. Specially, in human immunodeficiency virus (HIV)-infected people, the global prevalence was 19.96% (95% CI 16.18–23.74) for helminths and 34.18% (95% CI 31.33–37.03) for protozoa, respectively. The global prevalence of protozoa was 41.79% (95% CI 15.88–67.69) in hepatitis B virus (HBV)-infected people and 17.75% (95% CI 3.54–31.95) in DENV-infected people, respectively. The global burden of parasitic infections in HIV-infected people was 7,664,640 for helminths and 13,125,120 for protozoa, respectively, and that in HBV- and dengue virus (DENV)-infected people was 137,019,428 and 629,952, respectively. The prevalence of parasitic coinfection at the family, genus, and species levels in virus- or HIV-infected people were comprehensively estimated and further analyzed by subgroups. Among the most commonly identified parasites, the five helminth genera with the highest prevalence in HIV-infected people were Schistosoma (12.46%, 95% CI 5.82–19.10), Ascaris (7.82%, 95% CI 6.15–9.49), Strongyloides (5.43%, 95% CI 4.11–6.74), Trichuris (4·82%, 95% CI 2.48–7.17) and Ancylostoma (2.79%, 95% CI 1.32–4.27), whereas the top five protozoan genera were Toxoplasma (48.85%, 95% CI 42.01–55.69), Plasmodium (34.96%, 95% CI 28.11–41.82), Cryptosporidium (14.27%, 95% CI 11.49–17.06), Entamoeba (12.33%, 95% CI 10.09–14.57) and Blastocystis (10.61%, 95% CI 6.26–14.97). The prevalence of parasitic coinfection in virus-infected people was associated with income level. The findings provide valuable global epidemiological information for informing normative guidance, improving surveillance, and developing public healthcare strategies.